2009
DOI: 10.1186/1472-6947-9-18
|View full text |Cite
|
Sign up to set email alerts
|

What is the point: will screening mammography save my life?

Abstract: BackgroundWe analyzed the claim "mammography saves lives" by calculating the life-saving absolute benefit of screening mammography in reducing breast cancer mortality in women ages 40 to 65.MethodsTo calculate the absolute benefit, we first estimated the screen-free absolute death risk from breast cancer by adjusting the Surveillance, Epidemiology and End Results Program 15-year cumulative breast cancer mortality to account for the separate effects of screening mammography and improved therapy. We calculated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 66 publications
(97 reference statements)
0
19
0
2
Order By: Relevance
“…36 In comparison, columns C and D show the diagnosis risk for breast cancer and DCIS, 37 whereas column E shows the absolute death risk without screening mammography. 13 Barratt et al 38 show similar estimates for Australia. Without screening, over a decade a 50-year-old woman has a 5 times greater risk of receiving a diagnosis of breast cancer than of dying from it.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…36 In comparison, columns C and D show the diagnosis risk for breast cancer and DCIS, 37 whereas column E shows the absolute death risk without screening mammography. 13 Barratt et al 38 show similar estimates for Australia. Without screening, over a decade a 50-year-old woman has a 5 times greater risk of receiving a diagnosis of breast cancer than of dying from it.…”
mentioning
confidence: 82%
“…12 Therefore, the lowest life-saving proportion would be 3% (1/5 ϫ 1/7) in the larger subgroup of women who have been diagnosed with cancer. 13 The "pink ribbon" marketing 10,14 of breast cancer awareness supports advocacy groups and aims to increase the uptake of (participation in) mammography. Ostensibly for the sake of public health, the advertising campaign has some negative consequences.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 Studies have shown that 90% of women surveyed considered screening important in early detection and reduction of breast cancer mortality. 4 In a recent study Davis et al, 5 compared national and state-based estimates for the prevalence of mammography screening from the National Health Interview Survey (NHIS) and the Behavioral Risk Factor Surveillance System (BRFSS). They reported that the prevalence rates of women receiving mammography screening within the past 2 years increased from 73% in the period 1997-1999 to 76.7% in the period 2000-2003 among women aged ‡ 40 years.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] For younger women (< 50 years), the effectiveness of mammograms is controversial because it is related more with an increase in costs from unnecessary interventions than with reduced mortality. 25 During the agreement of the goals for the control of breast cancer in 2006, the Ministry of Health of Brazil recommended a biennial mammogram for women aged 50 to 69 years and an annual clinical breast examination for those aged between 40 and 49 years.…”
Section: Discussionmentioning
confidence: 99%